FIVE DIMENSIONAL BOOSTS AND ELECTROMAGNETIC FIELD IN KALUZA-KLEIN THEORY - Gladush, V. D.; Al-Shawaf, Nadim (Одеські астрономічні публікації, 2016)
A stationary, spherically symmetric, 5D Kaluza-Klein theory exhibits 5D boosts. After reduction of 5D vacuum Einstein action of a diagonal 5D metric, we obtained Einstein equations with energy-momentum tensor of a massless scalar field. Applying a 5D boost generates a non-diagonal metric with an electric field. This electric field is trivial, since it can be removed by a reverse 5D boost. Existence of such kind of trivial fields is analyzed on the example previously known solutions. Transformation properties of physical fields relative to 5D boosts examined. This symmetry is a subgroup of SL(3, R) symmetries of 5D equations, rewritten in 3 + 2-decomposition in stationary, spherically symmetric case. This symmetry also can be used to generate new solutions. The solution with trivial electric field is obtained from diagonal 5D metric by a simple symmetry transformation, which reduces to the coordinate 5D boosts.